Experimental and Numerical Investigations of Behavior of Rammed Aggregate Piers - Demir, S.; Ozener, P.; Kirkit, M. (AMER SOC TESTING MATERIALS, 2017)
This study presents the results from a series of laboratory tests carried out on rammed aggregate piers (RAPs) installed in different clayey sand beds formed in a large scale model test tank. The clayey sand beds were prepared by mixing 60 % sand, 40 % clay at a water content of 1.5 times the liquid limit of the clayey sand. The slurry mixtures were allowed to consolidate one-dimensionally until they reach different undrained strength values (c(u) = 2.5, 3, and 10 kPa). The diameter and length of RAPs were in the order of 10 cm and 60 cm, respectively for all the model tests carried out. The rammed aggregate piers were subjected to vertical loading at the top through a loading plate which was displaced by jacking of the installation system. Soil pressure cells were installed at different depths of the clayey sand bed to evaluate stress changes in them. Behavior of the single and group rammed aggregate pier and the surrounding soil were investigated by evaluating the measurements obtained from load tests and pressure cells. As a result of the laboratory tests, noteworthy results were obtained regarding the working mechanism of the RAPs in soils having different soil strengths, stress increases in the surrounding soil, and load sharing between the RAPs and the surrounding soil. A model test was also analyzed numerically and the results of laboratory measurements were compared with the numerical simulations. The results of the numerical analysis yielded reasonably close agreement with the experimental result.
Keywords: rammed aggregate pier; laboratory model test; ground improvement; numerical analysis; DISPLACEMENT PIERS; SUPPORT MECHANISMS; SOIL PRESSURE; STRESS ZONES; Engineering; Geology